2021
DOI: 10.1016/j.omto.2021.11.007
|View full text |Cite
|
Sign up to set email alerts
|

AAMP promotes colorectal cancer metastasis by suppressing SMURF2-mediated ubiquitination and degradation of RhoA

Abstract: Metastasis is considered the leading cause of cancer death due to the limited possibilities to therapeutically target this process. How the ubiquitination machinery contributes to metastasis remains underexplored. Angio-associated migratory cell protein (AAMP), a ubiquitously expressed protein involved in cell migration, has been reported to play oncogenic roles in breast and non-small cell lung cancer (NSCLC). However, the role of AAMP in colorectal cancer (CRC) has not been demonstrated. Here, we report that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…[ 68 ] AAMP has also been identified to promote colorectal cancer and NSCLC cell migration and invasion, further raising interest as a potential therapeutic target. [ 69 , 70 ] Because B7-H3 is also noted to play an important role in these cancer types, a combination approach targeting both B7-H3 and AAMP could be promising in NSCLC, CRC, and GBM.…”
Section: Discussionmentioning
confidence: 99%
“…[ 68 ] AAMP has also been identified to promote colorectal cancer and NSCLC cell migration and invasion, further raising interest as a potential therapeutic target. [ 69 , 70 ] Because B7-H3 is also noted to play an important role in these cancer types, a combination approach targeting both B7-H3 and AAMP could be promising in NSCLC, CRC, and GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that AAMP mainly locates in the cytoplasm and membrane of vascular endothelial cells, affecting the angiogenesis, diffusion, migration, and cytoskeleton remodeling processes of endothelial cells [ 25 , 26 ]. In addition, it has been reported that AAMP is abnormally up-regulated in metastatic CRC and boosts the occurrence of colorectal cancer by inhibiting SMURF2-mediated RhoA liquefaction and degradation [ 27 ]. Furthermore, AAMP is highly expressed in invasive gastrointestinal and breast carcinoma cells and is a marker of poor prognosis [ 4 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…FBX8 regulates the ubiquitination and stability of GSTP1, which inhibits the invasion and metastasis of CRC cells in vivo and in vitro [77]. SMURF2 acts as an E3 ubiquitin ligase to mediate the ubiquitination and degradation of RhoA, thereby decelerating the migration and invasion of CRC cells [79] (Figure 4).…”
Section: Ubiquitination Regulates Invasion and Migrationmentioning
confidence: 99%